Application and Development of Computer Science and Technology in the Era of Artificial Intelligence - Pei, Luhua (Journal of Theory and Practice of Management Science, 2025)
With the continuous progress and development of the times, computer technology is becoming more and more mature and the corresponding computers are also applied to the production and business activities of all walks of life. As an emerging technology, artificial intelligence has comprehensively promoted the rapid development of all walks of life. The effective integration of artificial intelligence technology in the computer field can realize the mutual promotion and common development of the two and also drive the rapid development of all walks of life. These are challenges to society, ethics, science and technology, morality, and other aspects in the era of artificial intelligence.